Acoustic Emission tomography based on simultaneous algebraic reconstruction technique to visualize the damage source location in Q235B steel plate. (December 2015) - Jiang, Yu; Xu, Feiyun; Xu, Bingsheng
Abstract: Acoustic Emission (AE) tomography based on Simultaneous Algebraic Reconstruction Technique (SART), which combines the traditional location algorithm with the SART algorithm by using AE events as its signal sources, is a new visualization method for inspecting and locating the internal damages in the structure. In this paper, the proposed method is applied to examine and visualize two man-made damage source locations in the Q235B steel plate to validate its effectiveness. Firstly, the Q235B steel plate with two holes specimen is fabricated and the pencil lead break (PLB) signal is taken as the exciting source for AE tomography.Secondly, A 6-step description of the SART algorithm is provided and the three dimensional(3D)image contained the damage source locations is visualized by using the proposed algorithm in terms of a locally varying wave velocity distribution. It is shown that the AE tomography based on SART has great potential in the application of structure damage detection. Finally, to further improve the quality of 3D imaging, the Median Filter and the Adaptive Median Filter are used to reduce the noises resulting from AE tomography. The experiment results indicate that Median Filter is the optimal method to remove Salt & Pepper noises. Highlights: Acoustic Emission tomography method based on SART for AE source location is proposed. The SART is first applied to AE filed, which is an effective image reconstruction technique. Internal structure image of object can be reconstructed from AE data by proposed algorithm. Increasing AE events will improve the quality of reconstructed 3D imaging. The 3D imaging can reveal the details of its internal structure to improve AE source location.